Causal theory, motor symptoms, non-motor symptoms, diagnosis, and treatment of Parkinson's Disease: a bibliographic review (Research, Society and Development, 2022)
Parkinson's Disease (PD) presents in senescence, limiting movement and progressing to dementia, thus being the second age-related neurodegenerative disease in the world. Thus, this literature review aims to gather relevant information about PD to direct new scientific approaches that will favor the clinical application, and thus, the quality of life of PD patients. Eighty studies published in the last 20 years were selected and analyzed in a database with indexed descriptors. The observed result leads to the understanding of causal theories, motor and non-motor symptoms, diagnosis, and treatment. It was concluded that the study guides, from the information gathered, new experimental studies to improve the quality of life of PD patients.